A Value-Chain Model for Research in Heritage Conservation: The Research Center for Heritage Conservation in Lima, Peru - Isa-Adaniya, Angélica (2022)
Even though funding for culture and heritage-related projects is normally scarce, it is even more difficult to find in times of crisis. One option to fund heritage protection is the acquisition of research and development funds, which usually require tangible achievements or an explicit link to socio-economic development. The Research Center for Heritage Conservation in Lima, Peru, adopted the value-chain model from the business management sector to evaluate and determine the convenience of embarking on a conservation project. This value-chain for heritage follows three stages: Identification and evaluation, conservation, and dissemination of results, to pave the way for the development of sustainable practices in collections management. Having limited human resources and infrastructure, projects had to comply with four criteria: a well-documented problem, a clear hypothesis or objective, a realistic methodology and a concrete set of practical and beneficial results. To illustrate these points, we offer an overview of five funded projects in our Center (gilded copper objects, archaeological gourds, colonial paintings, baroque altarpieces, and bespoke environmental sensors). The application of the value-chain model leads to tangible results which facilitate the initiation of a self-sustaining cycle for conservation research